2020
DOI: 10.1111/vru.12876
|View full text |Cite
|
Sign up to set email alerts
|

Inner ear fluid‐attenuated inversion recovery MRI signal intensity in dogs with vestibular disease

Abstract: The inner ear contains endolymph and perilymph. The second is comparable and in continuity with the cerebrospinal fluid (CSF) so it is expected to suppress in fluid‐attenuated inversion recovery (FLAIR) magnetic resonance imaging (MRI) if normal. Even though inner ear FLAIR abnormalities have been extensively described in humans with inner ear disease, its diagnostic value in dogs is yet to be proven. The goal of this retrospective cohort study was to investigate the diagnostic utility of FLAIR MRI in dogs wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
12
1
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 23 publications
(46 reference statements)
1
12
1
1
Order By: Relevance
“…Imaging findings in large felids with otitis media/interna were identical to those reported in domestic dogs and cats and included abnormal material within the tympanic bulla, bulla wall thickening, and alteration in normal fluid signal from the inner ear (40,41).…”
Section: Discussionsupporting
confidence: 53%
“…Imaging findings in large felids with otitis media/interna were identical to those reported in domestic dogs and cats and included abnormal material within the tympanic bulla, bulla wall thickening, and alteration in normal fluid signal from the inner ear (40,41).…”
Section: Discussionsupporting
confidence: 53%
“…The pathological mechanism of ISSNHL is currently not clear, which brings great challenges to the studies of etiology and therapeutics of ISSNHL . Recent studies have found that modern magnetic resonance imaging technology can detect abnormal changes in the labyrinth of the inner ear . Accumulating studies have confirmed that 3.0T MRI, especially the 3D-FLAIR sequence, has good sensitivity and specificity to the alterations in ISSNHL inner ear signals. , The application of 3D-FLAIR MRI can assist clinicians to find different pathological changes in the inner ear on time.…”
Section: Discussionmentioning
confidence: 99%
“…A laminated appearance of the mucosa of the tympanic bulla on T2W images has also been described (17). A reduced signal intensity on T2W or an increase signal intensity on FLAIR images from the intralabyrinthine fluid are MRI finding suggestive of otitis interna (14,16,18). Due to anatomical proximity, intracranial extension of OMI can lead to a meningeal enhancement (MgE) on MRI after intravenous administration of paramagnetic contrast medium (19).…”
Section: Introductionmentioning
confidence: 92%
“…14,15 A marked hyperintensity compared with adjacent structures is present on T2W images, while suppression is visible in FLAIR. 14,15 Postcontrast T1-weighted (T1W) images may show an abnormality consistent with inflammatory changes in the inner ear. 1 Typical changes raising the suspicion of OMI include isointense material in the bulla on T1W images and hyperintense on T2W images.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation